Dinâmica populacional de insetos fitófagos e predadores em cana-de-açúcar sob aplicação de silício - Otuka, Alessandra Karina [UNESP] (2015)
The use of silicon (Si) is a technique that increases plant resistance to insect pests. Also, it contributes significantly to the reduction of feeding activity and damage caused by these arthropods. This study evaluated the effect of Si application in two varieties of sugarcane on phytophagous and predators species of insects. The study aimed to verify the influence of this mineral on the abundance and diversity of species, analyze the population fluctuation of predominant species and their relationship with meteorological factors, and to identify the relationship between phytophagous and predator insects. Sugarcane varieties used were IAC-SP 963060 and IAC-SP 962042 and Si source used was calcium silicate and magnesium at a dose of 2.0 t ha-1. Sampling was performed every two weeks from February 2012 to January 2014. It was observed that the Si in varieties of sugarcane causes jaws wear of Atta sexdens (Linnaeus, 1758), it increases the incidence of Doru luteipes (Scudder, 1876) and Darditilla sp. and it decreases populations Gryllus spp. and Melanaphis sacchari (Zehntner, 1897). Application of Si does not change ants' diversity, but it reduces Mutillidae's and Staphylinidae's. The Si in sugarcane raises the population peaks of A. sexdens, Brachymyrmex sp., D. luteipes, Mahanarva fimbriolata (Stal, 1854). Sthetorus sp., Pheidole oxyops Forel, 1908, Scarites sp. 1 and Euborellia sp. are the predators most often associated to phytophagous insects in sugarcane. The maximum ambient temperature influences negatively D. luteipes and M. fimbriolata populations and minimum temperature does the same to Abaris basistriata Chaudoir, 1873, and Scarites sp. 1 populations. Increased rainfall reduces Syntermes sp. and Gryllus assimilis (Fabricius, 1775) populations